PERAN ZIS DALAM MENINGKATKAN KESEJAHTERAAN PEREMPUAN: Studi pada Program Bunda Mandiri Sejahtera Laznas Yatim Mandiri - Nabila Azzahra Tanjung (2023)
Zakat, infaq and alms (ZIS) play a role in alleviating poverty. However, Indonesia is still faced with the problem of poverty among women. Many of the heads of families are headed by women so that women have the potential to be empowered. The purpose of this study is to find out and analyze how the implementation of ZIS distribution through the BISA program is carried out by Laznas Yatim Mandiri and the implications for increasing the welfare of mustahik. This research is a descriptive statistical research and a case study. Data analysis used by researchers is in the form of data reduction, data presentation, and verification and conclusions. The data validity technique used by researchers is source and method triangulation. The findings of this study indicate that the mechanism for channeling ZIS through the BISA program is through the provision of religious, parenting, and economic studies, basic food assistance, assistance for orphans and dhuafa mothers, and business capital assistance. Then another finding, namely the BISA program has implications for spiritual and material values where from 15 (fifteen) Mustahik participants in the BISA program were in the material poverty index to 6 (six) Mustahik participants in the BISA program. Meanwhile, the welfare index from 0 (zero) mustahik became 9 (nine) participants in the BISA program.